Predicting child abuse potential : interplay of parents’ Aatachment histories, trauma, and quality of spousal relationship - Tepebağlı, Sena. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
aim of this study was to examine the relationship between child abuse potential and childhood traumas, attachment histories, and the quality of spousal relationships of parents with children aged 0-8 years in Turkey. A total of 769 parents (705 mothers and 64 fathers) participated in the study. Data were collected using the Brief Child Abuse Potential Inventory (Ondersma et al., 2005), the Three-Dimensional Attachment Styles Scale (Erzen, 2016), the Dyadic Adjustment Scale (Spanier, 1976), the Childhood Trauma Questionnaire (Bernstein et al., 1994), and a demographic form containing information about the parent and the child. Chi-square and hierarchical multiple regression analysis were used to analyze the data. Results indicated that childhood trauma history, attachment styles, parents' general health status, and quality of the relationship between spouses explained almost half (48.8%) of the variance in child abuse potential. While parents’ anxious- ambivalent attachment and childhood trauma history positively predicted child abuse potential, secure and avoidant attachment, general health status, the affective expression between spouses, and the dyadic satisfaction negatively predicted child abuse potential. This study contributes to the literature by addressing the intergenerational transmission of child abuse within the framework of attachment theory and examining both past and present family dynamics with the variables included.
Keywords: Child abuse -- Turkey.; Psychic trauma in children.